Temporal Trends and Regional Disparities in the Prevalence of Type 2 Diabetes–Related Complications in Iraq: A Population-Based Cohort Analysis - Hassan Rasan, Saja Salem Abdul (American Journal of Biology and Natural Sciences, 2026)
Background: Iraq is experiencing a growing epidemic of type 2 diabetes mellitus (T2DM) with an alarming increase in incidence and complications, but evidence on temporal trends and regional disparities is scant. Objective: To evaluate temporal trends and regional differences in T2DM complications between Iraq’s governorates from 2015-2023. Methods: This population-based cohort study assessed data from 847,293 adults with T2DM across five regions in Iraq from the National Diabetes Registry and Ministry of Health records. Results: The proportion of individuals with complications increased from 34.2% (2015) to 52.8% (2023) overall, while diabetic nephropathy increased the most (8.3% to 18.7%), and cardiovascular disease increased from 12.4% to 24.1%. The Kurdistan Region showed the lowest prevalence of complications (31.4%), while the southern governorates had the highest (64.2%). Urban living status were associated with lower complications than rural living status (OR 0.67, 95% CI: 0.63-0.71). Conclusion: Individuals with T2DM have increasing risk of complications across Iraq with significant regional differences, indicating a need for interventions and strengthened healthcare systems.